Limits of "Libog" ; And now ... the water crisis ; Discovering Yanni [videorecording] - Canlas, Ruben, Jr; Cantada, Candy; Lazaro, Cheche; Valdellon (The Probe Team, 1995)
Looks into the dismissal of some Miriam College students. They published a literary magazine called "Libog" and the school administration is not impressed. Looks also into the problem of Manila's water supply. Discover the music of Yanni Chrysomallis.